L' âme de ma lande campinoise - Wellens, Charles (Hasselt : s.n., 1951)
Bibliotheek Camille Huysmans
Dedicator: Wellens, Charles, dedicatee: Huysmans, Camille
Frans
Brochure
Keywords: volkscultuur; Vlaanderen